The Religious Revival in China - Hongyi Harry Lai (The Copenhagen Journal of Asian Studies, 2005)
Since 1979, China has experienced a widespread revival of religious faith and practice. This article aims to provide an overview of this phenomenon, by examining the causes behind it, the variety and popularity of religions and the different profi les of believers. It suggests that China's religions are diverse, encompassing offi cial, unoffi cial, and folk religions, and that the revival is signifi cant and visible. According to official statistics, the five largest religions in 2003 counted 144 million believers, while the non-offi cial sources give the figure as nearer 200 million. The revival has been fuelled by a number of factors: the state's lifting of the ban to freedom of worship; popular disillusion with the official ideology; economic and social uncertainties in the wake of economic reforms and modernization; and the enduring resilience of religion and tradition. For ethnic minorities like Uighurs and Tibetans, the revival of their religion has been accompanied by a similar cultural renaissance. Buddhists and Daoists among the Han in Hubei Province come from a wide range of educational backgrounds and professions, although the majority of them are women or were born before 1956. The Han Buddhists and Daoists turn to religion primarily for practical reasons, that is, to gain some advantage in their earthly lives rather than looking for rewards in the afterlife. For this reason, religious fundamentalism may have limited appeal to the Han Chinese.